Penerapan Model Floating House Berbasis Visualisasi 3D untuk Peningkatan Daya Saing Destinasi Wisata Perairan: Studi Kasus Pulau Qeis, Kampar - Fazli Abdisalam; Sefrona Syaiful; Rahma Putri Andita (TOBA: Journal of Tourism, Hospitality, and Destination, 2025)
This study aims to analyze existing conditions and development strategies of Pulau Qeis natural tourism in Kampar Regency and design a 3D visualization model as an innovation to enhance destination attractiveness. The research employed a qualitative descriptive approach with observation, in-depth interviews, and documentation techniques, involving Tourism Office, tourism managers, Pokdarwis, and local tourism activists. Data analysis used the Miles and Huberman model through data reduction, data presentation, and conclusion drawing stages. Results indicate that Pulau Qeis possesses strengths in diverse water-based attractions, active community participation, and environmental conservation commitment. Main weaknesses include limited utilization of promotional technology and facility damage due to fluctuating dam water levels. The 3D visualization model developed using Google SketchUp and Lumion software produced a floating house concept adaptive to geographical conditions while creating new tourist attractions. This visualization functions as both development blueprint and effective promotional medium. The study recommends integrated management strategies based on sustainable tourism, diversification of digital promotion technology, implementation of floating house concept to strengthen competitiveness, and systematic program development considering the balance between economic utilization and environmental conservation.